Bank Mergers and the Right to Bargain Collectively - Cacdac, Hans Leo J. (Philippine Journal of Labor and Industrial Relations, 2021)
Part I of this paper provides a brief narrative on the phenomenon of mergers in the banking industry. Part II renders a report on unionization in the banking industry. Part III surveys the Philippine and American jurisprudence on the effect of mergers on (1) the collective bargaining rights of an exclusive bargaining representative; and (2) any existing CBA at the time of the merger. Part IV discusses the modes of determining representation status under the Labor and its implementing rules and regulations. Part V presents the experience of two notable bank mergers in the last three years, namely between Equitable and PCI Bank and Bank of the Philippine Islands and Far East Bank and Trust Company. The last part provides possible remedies and courses of action.